Urgent Endovascular Treatment of Thoraco-abdominal Aneurysms Using a Sandwich Technique and Chimney Grafts - A Technical Description - Kolvenbach, R. R.; Yoshida, R. [UNESP]; Pinter, L.; Zhu, Y.; Lin, F. (W B Saunders Co Ltd, 2011)
Introduction: So far the only endovascular option to treat patients with thoraco abdominal aortic aneurysms is the deployment of branched grafts. We describe a technique consisting of the deployment of standard off-the- shelf grafts to treat urgent cases.Material and Methods: The sandwich technique consists of the deployment of ViaBahn chimney grafts in combination with standard thoracic and abdominal aortic stent grafts. The chimney grafts are deployed using a transbrachial and transaxillary access. These coaxial grafts are placed inside the thoracic tube graft. After deployment of the infrarenal bifurcated abdominal graft a bridging stent-a short tube graft is positioned inside the thoracic graft further stabilizing the chimney grafts.Results: 5 patients with symptomatic thoraco abdominal aneurysms were treated. There was one Type I endoleak that resolved after 2 months. In all patients 3 stentgrafts had to be used When possible all visceral and renal branches were revascularized. A total number of 17 arteries were reconnected with covered branches. During follow up we lost one target vessel the right renal artery.Conclusion: The sandwich technique in combination with chimney grafts permits a total endovascular exclusion of thoraco abdominal aortic aneurysms. In all cases off-the shelf products and grafts could be used. The number of patients treated so far is still too small to draw further more robust conclusions with regard to long term performance and durability. (C) 2010 European Society for Vascular Surgery. Published by Elsevier Ltd. All rights reserved.
Keywords: Thoraco-abdominal aortic aneurysms; Sandwich technique; Chimney grafts